Doehlert experimental design for the optimization of electrocoagulation treatment of landfill leachate. Issue 1 (1st January 2021) - Mansour, Dorsaf; El-Sofany, Walaa I.; Abdella, Faiza.I.A.; Masood, Najat; Khalaf Dhahi Alsukaibi, Abdulmohsen; Bellakhal, Nizar
ABSTRACT: The treatment of a mature landfill leachate has been studied by the electrocoagulation process using aluminum electrodes. In this study, Doehlert experimental design was applied for the determination of the optimal operating conditions. The results were evaluated through the construction of isoresponse contour plots and the latter showed that an initial pH of 6, an electrolysis time of 90 min and a current density of 15 mA‧cm −2 were optimal, leading to an almost total leachate remediation. Indeed, under these conditions removal rates of 94% of COD and 97% of color were achieved. In addition, the proposed models were found appropriate for the results prediction. The electrocoagulation can be recommended as a feasible and effective technology for the removal of pollutants from aqueous medium.